(untitled) (Anclajes, 2022)
From 1921 to 1923, El Tepozteco appeared in Mexico City. A biweekly publication on religion, science, literature, Mexican linguistics and varieties. Organ of the Tepozteca Colony in Mexico (Mexihco, Tepozteca Nechicolli). Nochi ipampa totlacatiliztlal (All for our homeland), under the direction of Nahuatl Mexican language professor and translator Mariano Jacobo Rojas. This article investigates some aspects of this printed periodical such as the characterization of its main audiences, the development of one of its main sections dedicated to the teaching of the Nahuatl language and which are the preamble for the writing of the Manual de la lengua náhuatl. Método práctico para hablar, leer y escribir la lengua americana, by Rojas published in 1927; as well as its financing and circulation strategies in the capital and the states of the Mexican Republic. The discovery of this print at the Library of the National Museum of Anthropology and History will allow an approach to the printed periodicals of enlightened indigenous people who participated in the complex and tense cultural framework that defined the scenario of the formation of the post-revolutionary state and its indigenist debates.